2012
DOI: 10.1016/j.jad.2012.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Why ruminators won't stop: The structural and resting state correlates of rumination and its relation to depression

Abstract: Note: This is an uncorrected version of an author's manuscript accepted for publication. Copyediting, typesetting, and review of the resulting proofs will be undertaken on this manuscript before final publication. During production and pre-press, errors may be discovered that could affect the content. AbstractBackground: Rumination is a good predictor of major depression. The current study explores

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
86
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 69 publications
9
86
2
1
Order By: Relevance
“…Numerous studies using event-related and resting-state fMRI designs point to alterations in ACC activity in depressed patients (26)(27)(28)(29). The first resting-state fMRI study with MDD patients revealed a hyperconnectivity between the subgenual ACC and the DMN, confirming previous PET studies, which found resting state overactivity in ACC in these patients (30).…”
Section: Discussionsupporting
confidence: 70%
“…Numerous studies using event-related and resting-state fMRI designs point to alterations in ACC activity in depressed patients (26)(27)(28)(29). The first resting-state fMRI study with MDD patients revealed a hyperconnectivity between the subgenual ACC and the DMN, confirming previous PET studies, which found resting state overactivity in ACC in these patients (30).…”
Section: Discussionsupporting
confidence: 70%
“…The fact that the involvement of dorsal areas might be a vulnerability factor is underscored by the observation that rumination is also associated with volume and resting state reductions in brain areas that have been linked to cognitive control processes such as prefrontal areas and the ACC (Kuhn, Vanderhasselt, De Raedt & Gallinat, 2012).…”
Section: A Cognitive Framework Of Depression and The Relationship Witmentioning
confidence: 99%
“…Another study comparing DMN and task-positive networks in MDD showed that ruminations were associated with increased DMN dominance at rest (Hamilton et al, 2011). Finally, by computing whole-brain correlation between RRS and resting state activity, Kühn, Vanderhasselt, De Raedt, and Gallinat (2012) found a negative relation with right inferior frontal gyrus, right ACC, and sgACC. They also found increased functional connectivity of the left striatum with left inferior frontal gyrus in healthy individuals experiencing more unwanted thoughts (Kühn, Vanderhasselt, De Raedt, & Gallinat, 2013).…”
Section: Introductionmentioning
confidence: 96%